2019
DOI: 10.1017/s0143814x19000126
|View full text |Cite
|
Sign up to set email alerts
|

Who feeds information to regulators? Stakeholder diversity in European Union regulatory agency consultations

Abstract: To design regulatory policies, agencies depend on information from the industries they are tasked to regulate. Therefore, agencies can organise consultations with the aim of obtaining information from different perspectives. This article focuses on stakeholder diversity in agency public consultations. We ask to what extent is information provided by stakeholders other than the regulated sector, such as other business interests, experts or nonbusiness interests? Stakeholder diversity is relevant as it may preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 58 publications
6
53
1
1
Order By: Relevance
“…Despite decades of privatisation (Thelle & Sonne, 2018), many such actors have close ties with governments. National public authorities are prevalent in EASA's consultations (Beyers & Arras, 2019), making H1a and H2a less likely. Furthermore, EASA has limited environmental decision-making competences, limiting its appeal to environmental interest groups.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite decades of privatisation (Thelle & Sonne, 2018), many such actors have close ties with governments. National public authorities are prevalent in EASA's consultations (Beyers & Arras, 2019), making H1a and H2a less likely. Furthermore, EASA has limited environmental decision-making competences, limiting its appeal to environmental interest groups.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the paper contributes to EU agency literature. Recent contributions in this area investigated EU agencies' interaction with interest groups (Arras & Braun, 2018;Beyers & Arras, 2019;Borrás et al, 2007;Chalmers, 2015;Pérez Durán, 2017. This paper builds on this trend by introducing and testing findings from the literature on US regulatory agencies in the context of EU agencies.…”
Section: The Research Question Of This Study Reads;mentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, previous research has indicated mixed results as to whether or not business groups or NGOs have better chances to maintain their advocacy activities (see Halpin & Jordan, , for discussions on this issue). An interesting implication might be that increased openness of global political venues could lead to more inequality than mobilization at venues where access is more exclusive and managed by the IO staff (see also Beyers & Arras, ). While we cannot test this hypothesis with the data at hand, this is certainly a relevant avenue for future comparative research.…”
Section: Resultsmentioning
confidence: 99%